1990
DOI: 10.1023/a:1015946123697
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The healing effect of human epidermal growth factor (hEGF) on open wounds was studied in rats. No improvement in wound healing was found by topical application of EGF alone to open wound sites. We found an ointment containing EGF and a protease inhibitor, nafamostat mesilate or gabexate mesilate, or gelatin accelerated the healing rate of open wounds. Significant increases in the dry weight of the wound site granulation tissue, uronic acid (as an index of acid mucopolysaccharide) and hydroxyproline (as an inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…In particular, the topical application of EGF has been shown to accelerate the healing rate of open wounds [18]. The present study also demonstrated that a topical treatment with a rhEGF ointment significantly reduced the wound closure time (at least 2 days) in a full thickness wound model compared with that of the animals treated with the ointment base only.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In particular, the topical application of EGF has been shown to accelerate the healing rate of open wounds [18]. The present study also demonstrated that a topical treatment with a rhEGF ointment significantly reduced the wound closure time (at least 2 days) in a full thickness wound model compared with that of the animals treated with the ointment base only.…”
Section: Discussionsupporting
confidence: 70%
“…There have been many studies aimed at developing a topical formulation with the sustained and stable pharmacological properties of recombinant human EGF (rhEGF) [14,18]. The wound healing properties of a topical rhEGF treatment have been reported in split- or partial-thickness skin wound in pigs and guinea pigs, respectively [2,15].…”
Section: Introductionmentioning
confidence: 99%
“…Arylthioureas have attracted great attention owing to their diverse biological activities as antiviral agents, herbicides, pesticides, plant growth regulators and chelating agents . Guanidinium‐based molecules also showed several biological activities such as cardiovascular dilators, antihistaminics, anti‐inflammatory agents, antidiabetics, antibacterial, antifungal, antiprotozoal, antiparasitic and antiviral . Lamy et al .…”
Section: Introductionmentioning
confidence: 99%
“…The tripeptide sequence RGD (Arg-Gly-Asp) is a common cell-recognition motif responsible for the binding of the integrin receptors [4]. Guanidinium-based molecules are extensively utilised as cardiovascular drugs [8], antihistaminines [9], antiinflammatory agents [10,11], antidiabetic drugs [12], antibacterial and antifungal drugs [13], antiprotozal and other antiparasitic drugs [14] and antiviral drugs [15]. Nonpeptide cyclic cyanoguanidines are HIV-1 protease inhibitors [6], while carboxylic guanidino analogs show activity as influenza neuroaminidase inhibitors [7].…”
Section: Introductionmentioning
confidence: 99%